Applying SERVQUAL: Using service quality perceptions to improve student satisfaction and program image - Gregory, Jess L. (Journal of Applied Research in Higher Education, 2019)
Purpose: Austerity approaches in higher education require choosing the highest leverage strategies of increasing student satisfaction. Attending to student perceptions of program/service quality (SERVQUAL) is a means to identify areas that have the greatest return on investment. The paper aims to discuss these issues. Design/methodology/approach: This study explores how a program has applied the SERVQUAL model and survey to identify areas for growth. Findings: The survey of 57 students in a cohort-based doctoral program demonstrated the smallest gaps (highest satisfaction) with the domains of empathy (1.33) and responsiveness (1.30) and the lowest with reliability (2.03), tangibles (1.97) and assurance (1.90). Practical implications: While not all of the five dimensions are within the purview of a program to address (some may require funding that is determined at a college or university level), many of the gaps can be addressed by adopting procedures and policies that increase transparency so that students can moderate their expectations and faculty and staff can provide reliable information. Additionally, the use of the SERVQUAL model provided this program with specific, actionable information that could be used to improve the program. Originality/value: The study includes a review of studies that have applied the SERVQUAL model in higher education. The application of SERVQUAL to a cohort-based doctoral program to identify program improvements and steward program image fits into a gap in the extant literature. © 2019, Emerald Publishing Limited.
14 citations (Crossref) [2023-10-31] tex.ids: lens.org/000-458-242-452-814, pop00269 tex.type: [object Object]
Keywords: Market-driven forces in education; SERVQUAL; Service quality; Student satisfaction; dept.edl; peer-reviewed